Does diabetes modify the triglyceride–glucose index associated with cardiovascular events and mortality? A meta-analysis of 50 cohorts involving 7,239,790 participants - Jun Zhang; Qiye Zhan; Zhihao Deng; Ling Lin; Zhaolan Feng; Huabin He; Deju Zhang; Huilei Zhao; Xiang Gu; Xiaoping Yin; Peng Yu; Xiao Liu (Cardiovascular Diabetology)
Abstract Introduction Previous studies highlighted the association between the triglyceride–glucose (TyG) index and cardiovascular events in patients with diabetes. However, whether diabetes affects TyG-cardiovascular diseases (CVD) is still unclear. This study aimed to evaluate the association between the TyG index and CVD risk, stratified by diabetes status, as well as the potential modifying effect of diabetic status. Methods/design The PubMed, Cochrane Library, and Embase databases were searched for studies on the associations between the TyG index and cardiovascular events and mortality in patients with and without diabetes from inception to December 2, 2024. The random effects model was employed to pool the effect sizes. Results A total of 50 cohort studies (7,239,790 participants) were included. The mean age of participants was 31.46 years (diabetes mellitus [DM]: 65.18; non-DM: 31.23), and 40.66% of participants were female (DM: 36.07%; non-DM: 40.70%). The associations between the TyG index and cardiovascular events (HR: 1.72 vs. 1.55, P = 0.55), major adverse cardiovascular and cerebrovascular events (HR: 2.02 vs. 1.91, P = 0.84), stroke (HR: 1.46 vs. 1.39, P = 0.77) and cardiovascular death (HR: 1.85 vs. 1.60, P = 0.56) were similar among DM and non-DM individuals. However, the associations between the TyG index and ischemic heart disease (IHD) (HR: 2.20 vs. 1.57, P = 0.03) as well as all-cause mortality (HR: 1.94 vs. 1.24, P = 0.01) were stronger in DM patients than in non-DM patients. Conclusion TyG index showed association with cardiovascular events, mortality, and all-cause mortality independent of diabetic status, with low to moderate certainty. The associations for IHD and all-cause death were stronger in diabetic patients than in individuals without diabetes. Future studies should explore the role of diabetes in the TyG index-associated CVD outcomes and mortality. Graphical abstract